DIALOGICAL COMMUNICATION STRATEGY ANALYSIS IN IMPROVING TEACHERS' CRITICAL AWARENESS WITH PAULO FREIRE'S APPROACH (Case Study of Strada Daan Mogot Vocational School, Tangerang City) - Laurantius Anggita Yudha Harnoko; Fabianus Fensi; Lasmery RM Girsang (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to explore the role of dialogic communication in increasing teachers' critical awareness through Paulo Freire's critical pedagogy approach. The background of this study is based on the reality of traditional education that still applies the banking education model, where teachers are the only source of knowledge and students are only passive recipients. This model closes the space for dialogue, reflection, and critical thinking. In contrast, Freire's approach emphasizes the importance of equal dialogue between teachers and students as a path to liberation and critical awareness. This study uses a qualitative method with a sociocultural approach and a constructivist paradigm. Data were collected through structured interviews with three teachers from vocational high schools who have different backgrounds, experiences, and involvement in reflective communities. The results of the study indicate that dialogic communication is understood as a process of open exchange of ideas. However, its implementation is still limited by structural obstacles such as time, a dense curriculum, and the hierarchical culture of schools. Teachers who are active in dialogic forums tend to have a higher critical awareness of educational issues. This study confirms that dialogic communication not only increases student participation but is also an effective strategy for forming reflective and transformative teachers. Systemic support is needed so that dialogic communication can develop sustainably in the educational environment.